Anthropometric and performance variables discriminating elite American junior male weightlifters - Fry, A. C.; Ciroslan, D.; Fry, M. D.; Leroux, C. D.; Schilling, B. K.; Chiu, L. Z. F. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study is to identify physical and performance variables that discriminate elite American junior-aged men weightlifters from nonelite performers. Using a cross-sectional design, multiple discriminant analysis was used to determine field tests identifying elite male junior weightlifters. Young men who were participants (n = 115) at the Junior National and Junior Olympics Weightlifting Championships volunteered as subjects (mean +/- SD age = 14.8 +/- 2.3 years). Elite weightlifters (n = 20) were identified as the top 17.5% of national-level competitors when weightlifting performances were adjusted for body mass using the Sinclair equation. All other weightlifters were classified as nonelite (n = 95). Test batteries were performed immediately upon completion of a national-level weightlifting competition. Variables measured included easily-administered field tests of physical dimensions and body composition, muscular strength and power, flexibility, and gross motor control. The resulting regression equations correctly classified 84.35% of the weightlifters as elite or nonelite. Five variables significantly contributed to the discriminant analysis (Wilks [LAMBDA]= 0.6637392, [chi]2= 44.880, df = 5, p < 0.0001, adjusted R2 = 0.67). Body mass index accounted for 23.13% of the total variance, followed by vertical jump (22.78%), relative fat (18.09%), grip strength (14.43%), and torso angle during an overhead squat (0.92%). The use of these 5 easily administered field tests is potentially useful as a screening tool for elite American junior men weightlifters.